The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpubh.2023.1184882
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of self-medication practice during the COVID-19 pandemic: implications for pharmacy practice in supporting public health measures

Abstract: IntroductionSince the COVID-19 pandemic, self-medication had become highly popular due to the risk of virus infection and overwhelming medical resources. Pharmacists are well-positioned to provide public health education and disease prevention. This study aims to provide an overview of the research about self-medication during COVID-19 and the role of pharmacists in ensuring the drug safety related to self-medication.MethodsDatabases (PubMed, Google Scholar, Scopus, EBSCO host, and Web of Science) were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 107 publications
0
7
1
2
Order By: Relevance
“…Other studies conducted in Columbia and Saudi Arabia also showed a higher prevalence of selftreatment, 60,61 pointing to the necessity for addressing the factors that drive individuals to self-medicate of which the most common were fears related to infection, quarantine, and societal stigma were the predominant motivations for selfmedication. 62,63 However, studies done on self-medication during COVID-19 pandemic in: United States 13%, Australia 11%, Germany 11%, Spain 9%, United Kingdom 9%, Mexico 8%, and Italy 8% 64 showed disparity with the current report which may be due to drug policies and better health infrastructure. Nonetheless, this reflects the heightened anxiety and concerns prevalent during the pandemic, emphasizing the need for clear communication and support mechanisms.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Other studies conducted in Columbia and Saudi Arabia also showed a higher prevalence of selftreatment, 60,61 pointing to the necessity for addressing the factors that drive individuals to self-medicate of which the most common were fears related to infection, quarantine, and societal stigma were the predominant motivations for selfmedication. 62,63 However, studies done on self-medication during COVID-19 pandemic in: United States 13%, Australia 11%, Germany 11%, Spain 9%, United Kingdom 9%, Mexico 8%, and Italy 8% 64 showed disparity with the current report which may be due to drug policies and better health infrastructure. Nonetheless, this reflects the heightened anxiety and concerns prevalent during the pandemic, emphasizing the need for clear communication and support mechanisms.…”
Section: Discussioncontrasting
confidence: 56%
“…The main issues with self-medication include resource waste, boosting pathogen resistance, and significant risks to health such as adverse effects, drug interactions, abuse, and extended pain are just a few of the problems that come with unsupervised medication. 27 , 28 Antimicrobial resistance is a worldwide issue attributed to self-medication, particularly in underdeveloped nations where drugs are readily accessible. 26…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a logical or deductive partitioning method was used, which included literature review and evaluation of the indicators of the construct to be measured. The literature review highlighted four dimensions critical to self-medication behavior: Avoidance (Sharif et al, 2012 ; Castillo Martínez and Pérez-Acosta, 2021 ; Zambrano Barriga and Cusme Torres, 2023 ), Prevention (Zheng et al, 2023 ), Influence (Burak and Damico, 2000 ; Anghel and Craciun, 2013 ; Zeb et al, 2022 ) and Attitude (Krueger et al, 2005 ; Parihar et al, 2018 ; Sulistyowatia et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Prevention, as discussed by Zheng et al ( 2023 ), encompasses actions taken to prevent disease or discomfort (Sharif et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation